Aortic Valve Sclerosis in High-Risk Coronary Artery Disease Patients - Myasoedova, Veronika A.; Genovese, Stefano; Cavallotti, Laura; Bonomi, Alice; Chiesa, Mattia; Campodonico, Jeness; Rondinelli, Maurizio; Cosentino, Nicola; Baldassarre, Damiano; Veglia, Fabrizio; Pepi, Mauro; Alamanni, Francesco; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: Current knowledge regarding the relationship between aortic valve sclerosis (AVSc), cardiovascular risk factors, and mortality in patients with known coronary artery disease (CAD) is still unclear. The present study aimed at investigating the prevalence of AVSc as well as its association with long-term all-cause mortality in high-risk CAD patients that has never been explored in large cohorts thus far. Methods and Results: In this retrospective and observational cohort study we enrolled high-risk CAD patients, hospitalized at Centro Cardiologico Monzino (CCM), Milan, Italy, between January 2006 and December 2016. The morphology and function of the aortic valve were assessed from the recorded echocardiographic images to evaluate the presence of AVSc, defined as a non-uniform thickening of the aortic leaflets with no consequences on hemodynamics. Data on 5-year all-cause mortality was retrieved from a Regional database. Of the 5,489 patients initially screened, 4,938 (mean age 67 ± 11 years, 3,954 [80%] men) were enrolled in the study. In the overall population, AVSc was detected in 2,138 (43%) patients. Multivariable LASSO regression revealed that age, female gender, diabetes mellitus, previous MI, and left ventricular ejection fraction were independently associated with AVSc. All-cause mortality (adjusted hazard ratio: 1.29, 95%CI: 1.05–1.58) was significantly higher in AVSc than in non-AVSc patients. Conclusions: AVSc is frequently detected in high-risk CAD patients and is associated with long-term mortality. Our findings corroborate the hypothesis that AVSc is an underestimated marker of systemic cardiovascular risk. Thus, AVSc detection may be used to improve long-term risk stratification of high-risk CAD patients.